2021
DOI: 10.1101/2021.01.12.426381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Male sex and age biases viral burden, viral shedding, and type 1 and 2 interferon responses during SARS-CoV-2 infection in ferrets

Abstract: SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) hospitalizations and deaths disportionally affect males and the elderly. Here we investigated the impact of male sex and age by infecting adult male, aged male, and adult female ferrets with SARS-CoV-2. Aged male ferrets had a decrease in temperature which was accompanied by prolonged viral replication with increased pathology in the upper respiratory tract after infection. Transcriptome analysis of the nasal turbinates and lungs indicated that femal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
2
3
0
Order By: Relevance
“…In a similar study significantly higher systemic levels of IFN-alpha2 were identified in females compared to levels in males [67]. In our recent study, we found that older adult male ferrets had a delayed type I interferon response when compared to adult females, with males lacking induction of essential antiviral genes including OASL, MIX1 and IDG15 which coincided with increased viral burden [68]. In our present study using the hamster model, all of our animals were male suggesting that investigation into sex-biases are needed to gain a full understanding of our observed type I interferon dysregulation.…”
Section: Plos Pathogenssupporting
confidence: 53%
“…In a similar study significantly higher systemic levels of IFN-alpha2 were identified in females compared to levels in males [67]. In our recent study, we found that older adult male ferrets had a delayed type I interferon response when compared to adult females, with males lacking induction of essential antiviral genes including OASL, MIX1 and IDG15 which coincided with increased viral burden [68]. In our present study using the hamster model, all of our animals were male suggesting that investigation into sex-biases are needed to gain a full understanding of our observed type I interferon dysregulation.…”
Section: Plos Pathogenssupporting
confidence: 53%
“…The prominent upper respiratory infection suggested the ferret to be useful for transmission studies and they have now demonstrated efficient aerosol and contact transmission of SARS-CoV-2 [ 85 , 87 , 146 , 147 ]. Our ferret study as well as others have found that nasal turbinate viral load was associated with rhinitis and nasal epithelium degeneration and necrosis [ 87 , 148 ]. Neutralizing antibodies against SARS-CoV-2 were apparent in some studies as early as day 8 pi correlating with virus clearance [ 85 , 87 ].…”
Section: Introductionsupporting
confidence: 72%
“…In a similar study significantly higher systemic levels of IFN-alpha2 were identified in females compared to levels in males 73 . In our recent study, we found that older adult male ferrets had a delayed type I interferon response when compared to adult females, with males lacking induction of essential antiviral genes including OASL, MIX1 and IDG15 which coincided with increased viral burden 74 . In our present study using the hamster model, all of our animals were male suggesting that investigation into sex-biases are needed to gain a full understanding of our observed type I interferon dysregulation.…”
Section: Discussionmentioning
confidence: 89%